Extraction and analysis of fixed oils from the seeds of Calophyllum inophyllum Linne (Fam. Guttiferae) (Bitaog) - Tabor, Juvy A.
The seeds of Calophyllum inophyllum Linne (Fam. Guttiferae), commonly known as ?bitaog? or ?palomaria?, was found to yield 64.24% (v/w) oil and contains plant acids and tannins.